Thera, the Aegean, Egypt, the Hyksos and Anatolia: rethinking the orthodox synchronisations and histories - Manning , Sturt W. (Journal of Greek Archaeology, 2024)
The Minoan eruption of the Thera volcano has come to offer a pivotal event in the synchronisation of Aegean and East Mediterranean civilizations. In relative (ceramic) terms the eruption occurred late in or around the end of the Late Minoan (LM) IA period. The date was traditionally placed around 1500 BCE, not from any specific evidence, but because some subsequent (late) LMIB objects were found in Egypt in contexts associated with Tuthmosis III, and, since his reign of almost 54 years was placed, give or take debates of up to 25 years, around the first half of the 15th century BCE, this led to a minimum date for the end of LMIA and Thera conveniently summarized as ca. 1500 BCE (Marinatos 1939; Warren 1984). This placed much of the LMIA period during the earlier New Kingdom. Radiocarbon dates from the 1970s onwards upset this position by suggesting an earlier date for Thera. This raised the prospect of an alternative cultural synchronisation for LMIA (and indeed MMIII-LMIA overall) with the Hyksos era (Second Intermediate Period, SIP): the Aegean high chronology (AHC). The AHC in turn would affect surrounding cultural groups and their dates in the Aegean and East Mediterranean, from Greece to Cyprus (Manning 1999). Much effort has gone into refining the radiocarbon situation. Since 2020 the options are an ‘earlier’ date maybe 1611 BCE (when a major Northern Hemisphere volcanic eruption is attested in ice-core evidence) or broadly around 1600 BCE (if, for example, the Thera eruption is not represented in the available ice-core evidence investigated so far), and a later date perhaps about 1561 BCE (when another major Northern Hemisphere volcanic eruption is attested in ice-core evidence) (Manning 2022; 2024a; 2024b; Pearson et al. 2022; 2023). Either of these dates basically places LMIA contemporary with the Hyksos/SIP (i.e. the point of the AHC critique starting in the 1980s: Kemp and Merrillees 1980; Betancourt 1987; Manning 1988). Overall, the general scope of debate or ‘dispute’ is much narrowed to around 50 years, versus the gap of over a century in scholarship a couple of decades ago. A re-analysis now of radiocarbon dates recently published on an olive shrub from Therasia likely killed by the Thera eruption (Pearson et al. 2023), bringing to bear an appropriate integration of the temporal constraints on these dates from both the growth sequences of the olive branches in question and the contextual circumstance of their common death event (the eruption) (Manning 2024b), along with analysis of the data and temporal sequence in the period between final human occupation and abandonment at Akrotiri on Thera through to the Thera volcanic eruption (Manning 2022; 2024a), suggest to the author that we can in fact more likely resolve the date of the Thera eruption around the earlier date of 1611 BCE (or more broadly around 1600 BCE).